2019
DOI: 10.1177/1553350619828900
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Prosthetic Mesh in the Emergency Management of Acute Incarcerated Inguinal Hernias

Abstract: Introduction. Tension-free hernia repair has been regarded as a gold standard treatment for selected inguinal hernias, but the use of prosthetic mesh in acute incarcerated inguinal hernias is controversial. Our study focused on evaluating the safety and efficacy of the prosthetic mesh repair for emergency cases. Methods. Patients with acute incarcerated inguinal hernias who underwent emergency prosthetic mesh repair during 2009 to 2014 at our department were included. Patient characteristics, operative approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…[13] Mesh infection is a major cause of inguinal hernia repair failure [14][15]. The results showed that the incidence of patch-related infection after tension-free repair of inguinal hernia was 0.6%-8.0% [16][17][18]. The total infection rate of laparoscopic herniorrhaphy was 0.7%-2%, which was related to the nonstandard aseptic operation, incomplete hemostasis, and contamination of the Mesh itself [19].…”
Section: Discussionmentioning
confidence: 99%
“…[13] Mesh infection is a major cause of inguinal hernia repair failure [14][15]. The results showed that the incidence of patch-related infection after tension-free repair of inguinal hernia was 0.6%-8.0% [16][17][18]. The total infection rate of laparoscopic herniorrhaphy was 0.7%-2%, which was related to the nonstandard aseptic operation, incomplete hemostasis, and contamination of the Mesh itself [19].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the use of a mesh for the tension-free repair of an emergency hernia does not seem to be an absolute contraindication 11 . A mesh is safe to apply even in cases of intestinal resection and anastomosis 10,[17][18][19][20] . Evidence has accumulated regarding the application of synthetic meshes, and clinicians recommend the use of synthetic meshes to repair FHs in patients, including in emergency situations 2,10,19 .…”
Section: Discussionmentioning
confidence: 99%